A comparative case study illustrating the influence of a system perspective on the outcome evaluation of simple versus complex interventions. (June 2023) - Renger, Ralph; Renger, Jessica; Van Eck, Richard N; Basson, Marc D; Renger, Jirina
When evaluating the effectiveness of an intervention, the evaluation approach must match the intervention complexity, ensuring that the chosen evaluation is "fit for purpose." For simple interventions, evaluating short-, mid-, and long-term outcomes is appropriate. However, for complex interventions, an additional outcome that must be considered is the essential system property that emerges as a result of the interaction of interdependent intervention components. By focusing on the emergent system property, evaluators are better able to assess the holistic effectiveness of a complex intervention. This article illustrates this principle through a comparative case study of a simple intervention and a complex intervention within a National Institute of Health (NIH) funded Clinical Translational Research center. The analysis illustrates that a more effective and appropriate evaluation results when a complex intervention, deemed to be operating and functioning as a system, is evaluated as a system than could have been achieved by treating each component as independent and evaluating the short-, mid-, or long-term outcomes of each component.